A review of post-operative imaging of zygomaticomaxillary complex fractures without orbital floor reconstruction in University Hospital Galway - E. Donohoe; R. Courtney; Z. Rasko; P.J. McCann; T. Barry (Elsevier, 2021)
The zygomaticomaxillary complex (ZMC) is used to describe the zygomatic bone and related structures. When ZMC fractures occur treatment ranges from conservative management to open reduction with internal fixation. It is recommended that radiographs are used to assess the outcome of surgical treatment. Additionally, it is advised that these radiographs are taken, and the images viewed prior to patient discharge.This study analysed the post-operative images used for ZMC reduction without orbital floor reconstruction over a five-year period in the Oral and Maxillofacial Surgery (OMFS) Department in University Hospital Galway (UHG).